Investigation and analysis of factors related to sleep conditions during the acute withdrawal period of alcohol use disorder - Liu, Xu; Kong, Xiangqi; Chen, Xu (Frontiers in Psychiatry, 2025)
ObjectivePatients with Alcohol Use Disorder (AUD) often experience significant mood disturbances and sleep disorders during the acute withdrawal period. This study aims to assess the sleep quality of AUD patients during acute withdrawal using polysomnography (PSG) and to evaluate their emotional states through standardized scales, to explore the role these factors play in the sleep quality of AUD patients during the acute withdrawal period.MethodsThe study’s experimental group consisted of fifty male patients, aged 18 to 66. Fifty healthy male volunteers served as the control group. On days 1–2 of alcohol withdrawal, PSG evaluated sleep processes, structural characteristics, and sleep-related breathing parameters in both AUD patients and the control group. The Pittsburgh Sleep Quality Index (PSQI), Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI), Penn Alcohol Craving Scale (PACS), and Barratt Impulsiveness Scale (BIS) were used to measure impulsivity, mood disorders, alcohol desire, and sleep quality, respectively. The use of multiple linear regression to analyze factors related to sleep disorders.ResultsCompared to the control group, AUD patients exhibited significantly reduced total sleep time, sleep efficiency, and rapid eye movement (REM) sleep, along with increased snoring frequency and duration. Additionally, AUD patients had significantly higher scores on the PACS, BDI, and BAI. Multiple regression analysis revealed that alcohol craving, depression, and anxiety were significantly associated with impaired sleep quality.ConclusionOur findings demonstrate that AUD patients experience significant sleep disturbances during the acute withdrawal period, influenced by alcohol craving, depression, and anxiety.